“The dead will rise” and “the doctors will resurrect” in the Book of Psalms by archbishop Ambrose (Zertis‑Kamensky), Masoretic text, Septuagint and Elisabethian Bible - Daria Vasilieva (Вестник Свято-Филаретовского института, 2023)
The article is dedicated to the idiom רְפָאִים יָקוּמוּ in the 2nd half of the Ps. 87:11 in the Church Slavonic, Greek, Masoretic texts, and in translation of the Psalms by archb. Ambrose (Zertis-Kamensky), from the Hebrew, which was made in the 18th century. The readers, interpreters and exegetes understood these words differently. The article presents an analysis of the variants of its translations, especially those that differ from the traditional. Furthermore, the translation of archb. Ambrose was made at the time, when the interpreting from the Masoretic text wasn’t favorite in Russian Church. The differences in the transference of these words are examined in the first part of the article. The distinctions of the interpretation of this idiom in the translations said above are analyzed for this reason. The Greek and Slavic texts need exegesis, and the Psalter doesn’t need any commentary. The probable theological sources of the analyzed Psalter are examined in the 2nd and 3rd parts. The translation of archb. Ambrose is compared with the Church Fathers, medieval theologians and exegetes, both west and Russian, for this reason. The first ones are St. Athanasius of Alexandria, St. Theodoret of Cyrus, St. Jerome of Stridon, Efthimius Zigaben and Cassiodorus. The second ones are M. E. Tate, S. Terrien and H.-J. Kraus. The comparison of their works and this Psalter is the foundation for the conclusions about existing parallels between them. The Fathers and this Psalter interpret only the general sense of the verse, but have different opinions on the idiom. There are more similarities with the interpretations of Western scholars-exegetes.